Molecular phylogeny of Moenkhausia (Characidae) inferred from mitochondrial and nuclear DNA evidence - Mariguela, Tatiane C.; Benine, Ricardo C.; Abe, Kelly T.; Avelino, Gleisy S.; Oliveira, Claudio (Hindawi, 2013)
Moenkhausia is one of the most speciose genera in Characidae, currently composed of 75 nominal species of small fishes distributed across South American hydrographic basins, primarily the Amazon and Guyanas. Despite the large number of described species, studies involving a substantial number of its species designed to better understand their relationships and putative monophyly are still lacking. In this study, we analysed a large number of species of Moenkhausia to test the monophyly of the genus based on the phylogenetic analysis of DNA sequences of two mitochondrial and three nuclear genes. The in-group included 29 species of Moenkhausia, and the out-group was composed of representatives of Characidae and other members of Characiformes. All species of Moenkhausia belong to the same clade (Clade C); however, they appear distributed in five monophyletic groups along with other different genera, which means that Moenkhausia is polyphyletic and indicates the necessity of an extensive revision of the group. © 2013 Blackwell Verlag GmbH.
Keywords: Biodiversity; Evolution; Molecular systematics; Neotropical fish; Phylogeny